Drying and storage conditions on the physical quality of Moti gome rice grains (Research, Society and Development, 2022)
Moti gome rice is characterized by its glutinous consistency and is very popular in Japanese cuisine. In general, rice is a cereal of great consumption worldwide and, being a seasonal product, its conservation and storage are justified. This work aimed to evaluate the effects of drying and storage conditions on the quality of Moti gome rice grains during their conservation. Rice drying was carried out under three conditions, that is, natural; artificial at 40 and 60 ºC and storage at two temperatures, 15 and 28 ºC for a period of 7 months. The physical qualitative characteristics (apparent specific mass and mass of one thousand grains), size and shape characterization, and benefit income (income, whole and broken yield) were evaluated. The results allow us to conclude that the artificially dried grains presented better physical quality when compared to those dried in the field. The type of drying did not promote important variations in the size and shape of the grains. The dry grain naturally has a lower whole yield than commercially required, lower yield and higher amount of broken grains.